Iowa spring 1995 report, Bill Huser - Huser, Bill F.et al (1995)
An annotated list of birds sighted by Bill Huser and others. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1995. Epson - sheet feed